Elevated circulating irisin is associated with lower risk of insulin resistance: association and path analyses of obese Chinese adults. Issue 1 (December 2016) - Shi, Xiulin; Lin, Mingzhu; Liu, Changqin; Xiao, Fangsen; Liu, Yongwen; Huang, Peiying; Zeng, Xin; Yan, Bing; Liu, Suhuan; Li, Xiaoying; Yang, Shuyu; Li, Xuejun; et al.
Abstract Background Evidence on the role of irisin in insulin resistance is limited and controversial, and pathways between them remain unknown. We aimed to examine the independent effects of circulating irisin and different adiposity measurements, as well as their potential interactions, on insulin resistance. We also aimed to explore possible pathways among circulating irisin, adiposity, glucose and insulin levels and insulin resistance. Methods A cross-sectional study of 1, 115 community- living obese Chinese adults, with data collection on clinical characteristics, glucose and lipid metabolic parameters and circulating irisin levels. Results Among the 1, 115 subjects, 667 (59.8 %) were identified as insulin-resistance, and showed significantly decreased serum irisin than their controls (log-transformed irisin: 1.19 ± 2.34 v.s. 1.46 ± 2.05 ng/ml, p = 0.042). With adjustment for potential confounders, elevated circulating irisin was significantly associated with reduced risk of insulin resistance, with adjusted odds ratio per standard deviation increase of irisin of 0.871 (0.765–0.991, p = 0.036). As for different adiposity measurements, body fat percentage, but neither BMI nor waist, was significantly associated with increased risk of insulin resistance (OR: 1.152 (1.041–1.275), p = 0.006). No significant interaction effect between serum irisin and adiposity on insulin resistance was found. A one pathway model about the relationship between serum irisin and insulin resistance fits well (χ 2 = 44.09, p < 0.001; CFI–0.994; TLI =0.986; and RMSEA = 0.067), and shows that elevated circulating irisin might improve insulin resistance indirectly through lowering fasting insulin levels (standardized path coefficient = −0.046, p = 0.032). Conclusions Elevated circulating irisin is associated with lower risk of insulin resistance indirectly through lowering fasting insulin.